Pengaruh Pergerakan Node Pada Protokol Routing Dynamic Manet On Demand (DYMO) Dalam Mobile Ad-Hoc Network (MANET) - Made Widya Anjani; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
One type of Ad-hoc Network is Mobile Ad-hoc Network (MANET) is a collection of nodes that can move and communicate in a network. The move node causes the topology on the MANET network to change frequently. In addition, there is a possibility that nodes will move away from neighboring communication range. It can increase the risk of path failures for connection and impact network performance. The mobility model of one another can produce different results on each routing protocol. Testing is required to select the appropriate mobility models. This research uses the Dynamic MANET On Demand (DYMO) routing protocol and is applied with the mobility models of Random Waypoint (RWP) and Random Direction (RD). The research was conducted using Network Simulator 2.35 to perform the scenario of adding the number of nodes, the addition of the simulation area and the addition of maximum speed. The test parameters for each scenario are packet delivery ratio (PDR), end-to-end delay, throughput and packet loss. The effect of RD movement when testing the area, causes the width of the distance between nodes because the node moves to the edge of the simulation area so that packet loss is high compared to RWP where the distance between nodes is shorter because the movement is random in the middle of the simulation area. The results showed an average PDR value for RWP of 98.60% while RD was worth 96.16%. Then the average packet loss for RWP is 1.40%, while RD is worth 3.84%.